Environmental & architectural phenomenology. Vol. 4, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 1993)
Vol. 4, No. 1, Winter 1993 (includes “items of interest,” "citations received,” conference report by J. Bruce May, poem by Gwendolyn Scott, and essays by Theodore Roszak, David Appelbaum, Robert Murgerauer & Jeffrey Wattles).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals